Türkiye's Offshore Hybrid Energy Potential and Cost Estimation in the Eastern Mediterranean - Çelikdemir, Soner; Özdemir, Mahmut Temel (My University, 2023)
In this study, for the first time, the focus is on determining the potential of renewable energy-derived hybrid energy in the Eastern Mediterranean region and conducting cost analysis for sample locations. The most important motivation of this study is that the Eastern Mediterranean zone has a significant hydrocarbon potential in addition to its geopolitical value, energy lines, and being a transportation route. Providing the energy needs of hydrocarbon platforms to be established in the region constitutes the main framework. For this, 6 zones determined were examined. Wind, solar, and wave energy potentials of these zones have been determined. If the energy is produced more than the needs of the platforms, it is planned to produce hydrogen by electrolysis. In this case, cost analyses of the system were carried out taking into account the situation of the hydrogen produced being transmitted to the mainland by different transport methods in the form of liquids or gases. According the results of the analyzes, it has been shown that the Eastern Mediterranean has a very high wind, solar, and wave energy potential due to the fact that Crete and Rhodes Islands form a natural strait. As a conclusion different transmission scenarios of the hydrogen to the mainland shows that the energy required by the platforms can be provided by renewable energy sources, regardless of their power.
Keywords: Cost Analysis; Hydrogen Production; Offshore Renewable Energy Sources; Hydrogen Transmission